2004
DOI: 10.1016/j.jacc.2004.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide and the progression of left ventricular dysfunction in experimental heart failure

Abstract: Tachycardic pigs given furosemide had significant acceleration of both contractile and metabolic features of CHF, including left ventricular systolic dysfunction, elevated serum aldosterone levels, and altered calcium handling in a controlled experimental model of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 33 publications
3
104
1
Order By: Relevance
“…23) Furosemide increased the urinary volume because of its potent natriuretic action, but increases in sCr, decreases in eGFR, exacerbation of the RAAS and conversely, aggravated renal dysfunction has also been reported. 20,23,27,28) In the present research, strong natriuresis was observed in the placebo group. The reason for this appeared to be that many patients in the placebo group used furosemide.…”
Section: Discussionsupporting
confidence: 52%
“…23) Furosemide increased the urinary volume because of its potent natriuretic action, but increases in sCr, decreases in eGFR, exacerbation of the RAAS and conversely, aggravated renal dysfunction has also been reported. 20,23,27,28) In the present research, strong natriuresis was observed in the placebo group. The reason for this appeared to be that many patients in the placebo group used furosemide.…”
Section: Discussionsupporting
confidence: 52%
“…Our results may provide basic information related to urine output and natriuresis as models of short-and longacting loop diuretics. Loop diuretic administration is associated with activation of neurohumoral axes such as the plasma concentrations of aldosterone, renin and norepinephrine [14,24,27,32]. However, the response of the RAA system to furosemide differs with diuretic duration.…”
Section: Discussionmentioning
confidence: 99%
“…Furosemide activates the RAAS and SNS, 4,5 accelerates LV dysfunction and elevates serum aldosterone. 24 In contrast, partial RAAS blockade could activate one or more RAAS components with resultant activation of angiotensin or aldosterone receptor, which is known as breakthrough phenomenon. 26 Thus, combination use of RAAS inhibitors and β-blockers with loop diuretics is important to improve prognosis in HF patients with low-dose loop diuretics.…”
Section: Combination Of Raas Inhibitors And/or β-Blockers With Loop Dmentioning
confidence: 99%